Bacteria induced cementation for soil stabilization - Cheng, L.; Shahin, Mohamed (2017)
© 2017 19th ICSMGE Secretariat. All rights reserved. In recent years, the use of microbiological processes to improve the mechanical properties of soil has gained some attention. This paper explores an emerging and promising biological soil stabilization technique, known as bio-cementation, using microbially induced calcite precipitation (MICP). In this work, uniform silica sand was treated using bio-cementation as well as ordinary Portland cement (OPC), and the results were compared in terms of the unconfined compressive strength (UCS) and permeability. The results indicate that bio-cementation is an effective soil stabilization technique in improving soil strength, with higher achieved UCS values and retained permeability than those of OPC-treated soil, demonstrating a major advantage for biocementation. The effectiveness of bio-cementation in harsh environment of extremely low and high temperatures was also examined, investigating the potential use of this technique in broader conditions in cold and arid regions. Furthermore, the performance of biocementation in marine environment was evaluated, showing the possibility of utilizing seawater as a natural calcium source to replace commercially available calcium chloride and demonstrating the feasibility of this technique in marine applications.